PENGATURAN PEMUTUSAN HUBUNGAN KERJA KARENA KESALAHAN BERAT DALAM PERJANJIAN KERJA BERSAMA ANTARA ADI PURWANTO (BURUH) DAN PT. MUJUR TIMBER SIBOLGA “(STUDI KASUS PUTUSAN HAKIM PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 178/PDT.SUS-PHI/2017/PN.MDN.) - Revaldi Sanjaya; Stanislaus Atalim (Jurnal Hukum Adigama, 2020)
Termination of employment (PHK) is a problem that always occurs in the world of work,termination of employment itself is a very frightening event for workers/laborers who face it, this is because it is related to the cessation/absence of financial income for the worker/laborer concerned to fulfill needs. Because it is a frightening event for workers, they must make every effort so that dismissal never occurs as reflected in Article 151 paragraph (1) of Law Number 13 Year 2003 concerning employment, however in practice this is unlikely to happen. occurs, in acompany there must be layoffs, one of which is layoffs due to serious mistakes. One example of layoffs due to serious errors is in Decision Number 178/PdtSus-PHI /2017/PN.Mdn, where Adi Purwanto as a worker was laid off due to a serious error stipulated in the Collective Labor Agreement that applies to the company where he works, the purpose of this research is to find out the validity of layoff regulations due to serious mistakes in Collective Labor Agreement . The methods used in this research are: This type of research is normative legal research which takesthe problem from the law then provides justification, the type of data used is primary legal material, secondary legal material, and tertiary legal material, data collection techniques used are used is literature study and interviews, and data analysis techniques are prescriptive techniques.